?-Glucanase-producing bacterial culture improves performance and nutrient utilization and alters gut morphology of broilers fed a barley-based diet - Onderci, M.; Şahin, Nurhan.; Cikim, G.; Aydin, A.; Ozercan, I.; Ozkose, E.; Şahin, Kazım (Elsevier Science Bv, 2008)
The present study was conducted to evaluate the efficacy of an Escherichia coli DH5-alpha strain producing beta-glucanase from Streptococcus bovis on growth performance, diet utilization and the gut morphology of broilers. One hundred and twenty 1-day-old chicks (Cobb 500) were randomly divided into three groups with five replicate pens of eight chicks and assigned to receive maize-based diet (MBD)(+), barley-based diet (BBD), BBD with addition of bacteria producing P-glucanase
Keywords: Broiler chickens; E. colic; Glucanase; Digestibility; Gut morphology